Exacerbation of asthma and airway infection: is the virus the villain? - Lusmaia D.C. Costa (Jornal de Pediatria, 2014)
OBJECTIVE: To review the available literature on the association between acute viral respiratory tract infection and the onset of asthma exacerbations, identifying the most prevalent viruses, detection methods, as well as preventive and therapeutic aspects. SOURCES: A search was conducted in PubMed, Lilacs, and SciELO databases, between the years 2002 and 2013, using the following descriptors: asthma exacerbation, virus, child, and acute respiratory infection. SUMMARY OF THE FINDINGS: A total of 42 Original Articless addressing the identification of respiratory viruses during episodes of asthma exacerbation were selected, mostly cross-sectional studies. There was a wide variation in the methodology of the assessed studies, particularly in relation to the children's age and methods of collection and viral detection. The results indicate that, in up to 92.2% of exacerbations, a viral agent was potentially the main triggering factor, and human rhinovirus was the most frequently identified factor. The pattern of viral circulation may have been responsible for the seasonality of exacerbations. The association between viral infections and allergic inflammation appears to be crucial for the clinical and functional uncontrolled asthma, but few studies have evaluated other triggering factors in association with viral infection. CONCLUSIONS: Respiratory viruses are present in the majority of asthmatic children during episodes of exacerbation. The involved physiopathological mechanisms are yet to be fully established, and the synergism between allergic inflammation and viral infection appears to determine uncontrolled disease. The role of other triggering and protective agents is yet to be clearly determined.